Performance of binary admixtures (Fly Ash and Silica Fume) on Self Compacting concrete. (2022) - Singh, Anjali; Mehta, P.K.; Kumar, Rakesh
Abstract: In the present study, M−30 grade Self Compacting Concrete (SCC) was designed using natural fine and coarse aggregates, Ordinary Portland Cement (OPC) and varying percentages of binary admixtures i.e., Fly Ash (FA) and Silica Fume (SF) for part replacement of OPC. Also, the effects of these admixtures in combination (FA + SF) were evaluated on the fresh properties, compressive strength, flexural strength, split tensile strength, cost and CO2 emission. Further, the micro-structural analyses (XRD and SEM) of different samples were carried out. The strength of different SCCs increases in the range of 4.34–44.88 % depending upon the type of admixture(s) or their combination and number of days. The cost of SCC reduces in the range of 2.77–10.97 %, when OPC is replaced in part by different admixtures or their combination. The reduction of CO2 emission lies in the range of 8.84–22.10 %, when OPC is replaced by admixture. Thus, the results show that the concrete containing either FA or binary admixtures are not only stronger and economical but also helpful in the environmental protection.